A rapid, gentle and scalable method for dissociation and fluorescent sorting of imaginal disc cells for mRNA sequencing. Issue 2 (2nd April 2016) - Khan, Sumbul Jawed; Abidi, Syeda Nayab Fatima; Tian, Yuan; Skinner, Andrea; Smith-Bolton, Rachel K.
ABSTRACT: Dissociation of imaginal disc cells has been carried out previously to enable flow cytometry and cell sorting to analyze cell cycle progression, cell size, gene expression, and other aspects of imaginal tissues. However, the lengthy dissociation protocols employed may alter gene expression, cell behavior and overall viability. Here we describe a new rapid and gentle method of dissociating the cells of wing imaginal discs that significantly enhances cell viability and reduces the likelihood of gene expression changes. Furthermore, this method is scalable, enabling collection of large amounts of sample for high-throughput experiments without the need for data-distorting amplifications.